Influence of palm oil fuel ash on the high strength and ultra-high performance concrete : A comprehensive review - Hamada, Hussein Mahmood; Abed, Farid; Alattar, Alyaa; Fadzil, Mat Yahaya; Tayeh, Bassam A.; Aisheh, Yazan I.Abu (Elsevier B.V., 2023)
In recent days, the increase in significant infrastructure projects has led to urgent requirements for the use of high strength concrete (HSC) and ultra-high-performance concrete (UHPC). However, the use of cement and its derivative products, such as concrete, is associated with a high generation of carbon dioxide (CO2). The construction industry contributes about 8% of the total global CO2 production. Therefore, there is an urgent need to use agriculture-waste materials such as palm oil fuel ash (POFA) to help reduce environmental concerns associated with concrete. The accumulation of palm oil waste over an extended period of time causes environmental pollution. The use of these materials is expected to improve the environment by reducing the disposal of this waste in landfills and open areas. The chemical composition of POFA can vary depending on the source and processing methods. Elevated levels of impurities such as organic matter, unburned carbon, and chloride content in POFA can adversely affect the setting time, workability, and long-term durability of concrete. The optimal mix proportioning and replacement levels of POFA in concrete need to be carefully determined. Incorporating higher levels of POFA without proper adjustments to the mix design can result in detrimental effects on fresh and hardened concrete properties, including reduced compressive strength and decreased resistance to chemical attacks. This paper will highlight the impacts of POFA on the properties of HSC and UHPC in their fresh and hardened states. Durability and microstructure properties were also discussed. The use of ultrafine POFA helped in reducing the rapid chloride permeability and water absorption of HSC, thus improved its structure. Lastly, some recommendations for future studies are presented.